Penalized quasi-likelihood estimation in partial linear models - Mammen, Enno; Geer, Sara van de (The annals of statistics, 1997)
Consider a partial linear model, where the expectation of a random variable Y depends on covariates (x,z)(x,z)(x, z) through F(θ0x+m0(z))F(θ0x+m0(z))F(θ_0 x + m_0(z)), with θ0θ0θ_0 an unknown parameter, and m0m0m_0 an unknown function. We apply the theory of empirical processes to derive the asymptotic properties of the penalized quasi-likelihood estimator.